1998
DOI: 10.2134/jpa1998.0180
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Effects on Triticale Grain Yield, Amino Acid Composition, and Feed Nutritional Quality for Swine

Abstract: Nitrogen fertilizer recommendations for triticale (X Triticosecale Wittmack) and soft red winter (SRW) wheat (Triticum aestivum L.) in the southeastern USA are similar in spite of different end uses. Grain yield, protein, and amino acid composition of four triticale cultivars were evaluated over five N levels ranging from 30 to 150 lb/acre in four Georgia environments. Nitrogen was topdressed as ammonium nitrate at peak tillering. Relative economic value of triticale for feed was calculated assuming total repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 14 publications
1
10
0
2
Order By: Relevance
“…Usually, when protein concentration increases there is a decrease in the lysine concentration (Bruckner et al 1998, Fernandez-Figares et al 2000. N fertilizer applied at the plant development stage EC47 increased lysine concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, when protein concentration increases there is a decrease in the lysine concentration (Bruckner et al 1998, Fernandez-Figares et al 2000. N fertilizer applied at the plant development stage EC47 increased lysine concentration.…”
Section: Discussionmentioning
confidence: 99%
“…With the extensive use of fertilizers in agroecosystems, the maternal effects of nutrition on seed quantity and quality have been studied intensively in agronomic and vegetable crops. In numerous studies with cultivated species, increased mineral nutrition has been shown to increase both seed mass and the concentrations of mineral nutrients and amino acids in seeds (Gray & Thomas, 1982; Altman et al , 1983; Fenner, 1992; Bruckner et al 1998; Oikeh et al , 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In studies done with rye ( Secale cereale L.) cover crops, reductions in the mass of leached N ranged from 59 to 77% compared with no cover crop (Meisinger et al, 1991). Production of winter triticale could provide fall and spring forage supplies when other sources are unavailable (Lyon et al, 2001) and allow grain to be harvested and used as a high quality swine feed (Bruckner et al, 1998). To capture these potential benefits from triticale, proper agronomic production practices must be determined.…”
mentioning
confidence: 99%